2021
DOI: 10.5194/aab-64-257-2021
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of sterigmatocystin exposure in cattle by difructose anhydride III feed supplementation and detection of urinary sterigmatocystin and serum amyloid A concentrations

Abstract: Abstract. We evaluated the effects of supplementing cattle feed with difructose anhydride III (DFA III) by measuring urinary sterigmatocystin (STC) concentrations using 20 Japanese Black cattle aged 9–10 months from one herd. DFA III was supplemented for 2 weeks for 10 animals, and non-treated animals served as controls. The natural STC concentration in the dietary feed was 0.06 mg kg−1 (mixture of roughage and concentrate) at the beginning of the study (Day 0). The urine STC concentration was measured using l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In addition, treatment of such oligosaccharides was proposed to restore the impaired epithelial barrier functions in the small intestinal epithelial cells [ 8 , 28 ]. We have also reported the effects of DFA III supplementation on calf/cattle, where we showed that supplementing DFA III with milk replacer reduced the onset of diseases, such as fever and diarrhea, during the pre-weaning period [ 17 , 18 ], and the effect of supplementing DFA III on feed-related epithelial barrier functions to reduce the absorption of mycotoxins, such as ZEN and STC, from the intestinal tract by measuring their urinary concentrations [ 19 , 20 ]. As a stepping-stone to elucidate the effects of DFA III supplementation on cattle health and intestinal defense function, in this study, we aimed to confirm whether the addition of DFA (40 g/days) to the diet increased the production of fatty acids in the intestinal tract and caused a difference in the serum concentrations of SCFAs after absorption from the intestinal tract.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, treatment of such oligosaccharides was proposed to restore the impaired epithelial barrier functions in the small intestinal epithelial cells [ 8 , 28 ]. We have also reported the effects of DFA III supplementation on calf/cattle, where we showed that supplementing DFA III with milk replacer reduced the onset of diseases, such as fever and diarrhea, during the pre-weaning period [ 17 , 18 ], and the effect of supplementing DFA III on feed-related epithelial barrier functions to reduce the absorption of mycotoxins, such as ZEN and STC, from the intestinal tract by measuring their urinary concentrations [ 19 , 20 ]. As a stepping-stone to elucidate the effects of DFA III supplementation on cattle health and intestinal defense function, in this study, we aimed to confirm whether the addition of DFA (40 g/days) to the diet increased the production of fatty acids in the intestinal tract and caused a difference in the serum concentrations of SCFAs after absorption from the intestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ], Sasazaki et al . [ 20 ]. Briefly, JB female heifers from two beef herds (Herd 1: n = 10; Herd 2: n = 20; approximately 10 months old and weighing 250–300 kg) raised in Kagoshima Prefecture, Japan, were included in this experiment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we have established a urinary ZEN-monitoring system with ELISA for initial screening purposes, followed by LC-MS/MS validation to detect ZEN and its related metabolites; α-zearalenol (α-ZEL) and β-zearalenol (β-ZEL) as well as sterigmatocystin (STC), as both toxins might occur together in diets for Japanese cattle [10][11][12]. Additionally, we have reported that monitoring ZEN or STC levels in urine is not only a practical and useful way of evaluating and detecting the naturally contamination status of cattle herds, but also assessing the efficiency of mycotoxin adsorbents (MAs) supplemented in dietary feed to reduce intestinal absorption of mycotoxins [10,11,13,14].…”
Section: Introductionmentioning
confidence: 99%